show that (cotA-1+cosecA) /(CotA+1-cosecA)=cotA+cosecA​

Question

show that (cotA-1+cosecA) /(CotA+1-cosecA)=cotA+cosecA​

in progress 0
Brielle 1 month 2021-08-18T23:46:21+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-18T23:47:34+00:00

    \huge\boxed{\underline{\underline{\green{\tt Solution}}}}

      \displaystyle \: \frac{CotA - 1 + CosecA}{CotA  + 1  - CosecA}

     =   \displaystyle \: \frac{CotA  + CosecA - 1}{CotA    - CosecA + 1}

     =   \displaystyle \: \frac{CotA  + CosecA - ( {Cosec}^{2}A -  {Cot}^{2}A)  }{CotA  + 1  - CosecA}

     =\frac{(CotA  + CosecA )-(CosecA  + CotA )(CosecA   -  CotA ) }{CotA  + 1  - CosecA}

     =   \frac{(CotA  + CosecA )(CotA  + 1  - CosecA)}{(CotA  + 1  - CosecA)}

     = (CotA  + CosecA)

    0
    2021-08-18T23:47:58+00:00

    Answer:

    ey Friend 🙂

    Here is your answer

    => 1 / (cosecA – cotA) . . . . . . . . . . .multiply top & bottom by (cosecA + cotA)  

    => (cosecA + cotA) /(cosec^2A – cot^2A) . . . . . . .use cosec^2A = 1 +                                                                                                                        cot^2A  

    => (cosecA +cotA) / 1  

    => cosecA + cotA

    RHS = LHS  

    Hence, proofed.

    i think it helped you

    kindly mark me as brainlist

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )